IMPLEMENTASI METODE MEASUREMENT OF ALTERNATIVES AND RANKING ACCORDING (MARA METHOD) DALAM SISTEM PENDUKUNG KEPUTUSAN PENENTUAN APARATUR DESA SINAH KASIH - Torong, Adi Putra S.; Hondro, Rivalri Kristianto; Fadlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Sinah Kasih is the name of a village in the Sei Rampah sub-district, Serdang Bedagai Regency, North Sumatra Province. The village government system of Sinah Kasih is directly led by a village head, who is democratically elected by the local community. The presence of village officials is crucial in supporting the village head in making policy decisions and implementing work-based programs that benefit Sinah Kasih. Currently, the selection of village officials in Sinah Kasih is directly carried out by the village head, but several issues have arisen, causing suspicion among the community. This suspicion stems from a lack of trust in the selection process, which is perceived to involve nepotism, leading to decreased community support for the village government's programs. As a result, the village head is seeking a solution to ensure the selection of village officials is more transparent and free from nepotism. A decision support system is a suitable solution to address the problems faced by the village head of Sinah Kasih. An application was developed to assist in decision-making processes by the village head. The outcome of the research is the design and development of a decision support system application, compatible with Windows, which functions as a tool for determining village officials in Sinah Kasih using the Measurement of Alternatives and Ranking According (MARA) method.